2007
DOI: 10.1194/jlr.r700001-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Remnant-like lipoprotein particles impair endothelial function: direct and indirect effects on nitric oxide synthase

Abstract: Remnant-like lipoprotein particles (RLPs) have been implicated as potentially atherogenic lipoproteins. Endothelial dysfunction is known to be an early event in atherosclerosis and an important contributor to the pathogenesis of coronary artery disease. Moreover, there is considerable evidence linking increased RLP cholesterol levels with endothelial dysfunction, reflected by impaired endothelial vasodilatation and abnormal endothelial secretion Remnant-like lipoprotein particles (RLPs), also known as remnant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(39 citation statements)
references
References 78 publications
0
34
0
5
Order By: Relevance
“…It is well established that oxidized low-density lipoproteins (ox-LDL) plays a role in atherogenesis by inducing EC apoptosis and increasing endothelial permeability [138]. Recently, it has also been revealed that remnant lipoprotein particles impair endothelial function via direct and indirect effects on endothelial nitric oxide synthase (eNOS) and by stimulating secretion of inflammatory factors, such as CRP, IL-6, and TNF-a, from multiple origins [139]. Remnant lipoproteins may accelerate senescence of endothelial progenitor cells through inhibiting telomerase activity via the reactive oxygen species-dependent pathway or altering microRNA levels eventually resulting in endothelial dysfunction and promoting the entry and retention of remnant lipoprotein particles in the vessel wall [140,141].…”
Section: Lipolytic Products Act On Vecs To Promote the Entry Of Lipopmentioning
confidence: 99%
“…It is well established that oxidized low-density lipoproteins (ox-LDL) plays a role in atherogenesis by inducing EC apoptosis and increasing endothelial permeability [138]. Recently, it has also been revealed that remnant lipoprotein particles impair endothelial function via direct and indirect effects on endothelial nitric oxide synthase (eNOS) and by stimulating secretion of inflammatory factors, such as CRP, IL-6, and TNF-a, from multiple origins [139]. Remnant lipoproteins may accelerate senescence of endothelial progenitor cells through inhibiting telomerase activity via the reactive oxygen species-dependent pathway or altering microRNA levels eventually resulting in endothelial dysfunction and promoting the entry and retention of remnant lipoprotein particles in the vessel wall [140,141].…”
Section: Lipolytic Products Act On Vecs To Promote the Entry Of Lipopmentioning
confidence: 99%
“…The RLp may affect the autophosphorylation of focal adhesion kinase and its downstream phosphatidylinositol kinase/Akt signalling pathway, resulting in direct eNOS inactivation through the induction of intracellular ROS. In addition, RLp might indirectly affect the expression or activation of eNOS by stimulating secretion of various inflammatory factors (for a review, see Zheng and Liu 2007).…”
Section: Role Of Oxidative Stress and Control Of Leucocyte Trafficmentioning
confidence: 99%
“…These elevated levels of TG-rich lipoproteins and their remnants have been shown to be linked to plaque formation and progression [16]. TG-rich lipoprotein remnants are also thought to contribute to the progression of atherosclerosis by indirect mechanisms such as impaired vasodilation and increased inflammation [5,[17][18][19][20].Therefore, the management of hypertriglyceridemia is important not only in the prevention of pancreatitis, but also in reducing the risk of CVD in patients with mild to moderate hypertriglyceridemia.The addition of niacin, fibrates, or long-chain omega-3-fatty acids to statin therapy has been advocated for those hypertriglyceridemic patients who have not attained normal TG levels [4][5][6][7][8][9]. However, these agents often differ substantially in their TG-lowering effects and associated adverse effects.…”
mentioning
confidence: 99%
“…These elevated levels of TG-rich lipoproteins and their remnants have been shown to be linked to plaque formation and progression [16]. TG-rich lipoprotein remnants are also thought to contribute to the progression of atherosclerosis by indirect mechanisms such as impaired vasodilation and increased inflammation [5,[17][18][19][20].…”
mentioning
confidence: 99%